Deposition Techniques for Transparent Conducting Thin-Films on Glass and Polymer Substrates Transparente und leitfähige Veredelung von Kunststoffoberflächen: Antistatische und elektrooptische Anwendungen - Abendroth, Thomas; Liebich, Jens; Härtel, Paul; Schumm, Benjamin; Althues, Holger; Kaskel, Stefan; Beyer, Eckhard (Vakuum in Forschung und Praxis, 2015)
We report on thin films deposited at atmospheric pressures on glass and polymer substrates with various techniques. The introduced thin-film materials show intrinsic properties being suitable for different applications while maintaining the principle properties of the substrates themselves (e. g. shape. rigidity/flexibility, transparency). With the main focus on optical and electronic applications the properties of the deposited films can be adjusted by the choice of coating material (e. g. metal oxide, CNT), the film's shape (compact, particulate) and the deposition process itself. We compare deposition and properties of different TCO-materials with CNT-based thin film techniques and demonstrate approaches for the integration of these processes in production lines.
CRIS-Team Scopus Importer:2023-03-20